1974
DOI: 10.1172/jci107890
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Saline-Induced Natriuresis upon Exposure of the Kidney to the Physical Effects of Extracellular Fluid Volume Expansion

Abstract: A B S T R A C T In many previous studies, the natriuresis induced by saline loading has been demonstrated to persist even though glomerular filtration rate (GFR) has been decreased to below pre-expansion levels by a reduction in renal artery pressure. In such studies, however, the kidney has been exposed to the effects of volume expansion for varying periods of time before renal artery pressure was controlled. The present experiments were designed to evaluate whether this period of exposure induces critical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
2

Year Published

1976
1976
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
0
20
1
2
Order By: Relevance
“…As shown in Fig. 2 (2) showed in rats that the natriuresis induced by saline loading was largely abolished when renal perfusion pressure was reduced to -70 mm Hg immediately before (EC), but not after (LC), the volume load. These findings, which have since been confirmed by others (3)(4)(5)(6), were also duplicated in the present study.…”
Section: Microvascular Resistances In Lc Vs Ecmentioning
confidence: 82%
See 3 more Smart Citations
“…As shown in Fig. 2 (2) showed in rats that the natriuresis induced by saline loading was largely abolished when renal perfusion pressure was reduced to -70 mm Hg immediately before (EC), but not after (LC), the volume load. These findings, which have since been confirmed by others (3)(4)(5)(6), were also duplicated in the present study.…”
Section: Microvascular Resistances In Lc Vs Ecmentioning
confidence: 82%
“…In view of these observations, the authors of these various studies have suggested that intrarenal, rather than plasma compositional or circulating humoral, factors were primarily responsible for these differing reabsorptive responses to early vs. late clamping. Moreover, insofar as systemic protein concentration (4) and filtration fraction (2) were affected equally by early and late clamping, these studies might also be taken as evidence against a role for postglomerular oncotic pressure as a major determinant of these differing sodium reabsorptive responses. Without an evalua-tion of the remaining transcapillary Starling forces, however, a meaningful assessment of the role of peritubular physical factors under these conditions is not possible.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Acute saline VE in th e ad ult results in signi ficant increases in RIHP and sodium excretion (6). When th e rise in RIHP is prevented from in creasing during VE in the adult, the increase in sodium excretion is signific antly attenuated (7,8). Furthermore , direct increa ses in RIHP comparable to the RIHP measured during VE result in significa nt increases in sod iu m excretion (9).…”
mentioning
confidence: 99%